Structural and composition irregularities in GaAs:Si/GaAs films grown by liquid-phase epitaxy - Kladko, V.P.; Datsenko, L.I.; Maksimenko, Z.V.; Lytvyn, O.S.; Prokopenko, I.V.; Zytkiewicz, Z. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Stoichiometry parameters as well as the microdefects ones for GaAs:Si/GaAs thin films grown by liquid-phase epitaxy were investigated by means of method of X-ray integrated reflectivity energy dependencies analysis for quasiforbidden reflections (200) in the interval of wavelengths near absorption K-edges of GaAs components.